2013
DOI: 10.3174/ajnr.a3692
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Middle Cerebral Artery Aneurysms with Flow Modification with the Use of the Pipeline Embolization Device

Abstract: BACKGROUND AND PURPOSE:The Pipeline Embolization Device was reported to be safe and effective in the treatment of sidewall aneurysms, preserving the patency of the vessels covered by the construct. However, to date, the safety and efficacy of this device in treating bifurcation aneurysms remains unknown. We report our preliminary experience with the use of the Pipeline Embolization Device in the management of MCA aneurysms located at the bifurcations, including mid-and long-term follow-up data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(100 citation statements)
references
References 26 publications
2
96
1
1
Order By: Relevance
“…The aneurysms treated with this technique were very challenging, and though anatomic results were superior in other FDS studies (80%-92%), [28][29][30] better results could be achieved with other techniques.…”
Section: 27mentioning
confidence: 73%
See 1 more Smart Citation
“…The aneurysms treated with this technique were very challenging, and though anatomic results were superior in other FDS studies (80%-92%), [28][29][30] better results could be achieved with other techniques.…”
Section: 27mentioning
confidence: 73%
“…Very recently, some articles investigating their use in the treatment of MCA aneurysms were published, though study populations were sometimes heterogeneous and included saccular and fusiform aneurysms and both bifurcation and nonbifurcation types. 28 reported good results, with 84% complete occlusion at follow-up. Although the last follow-up showed that 43% of covered branches had reduced caliber or were occluded, no permanent neurologic deficits occurred.…”
Section: 27mentioning
confidence: 94%
“…Most larger flow-diversion series either did not report any cases of devices of Յ3 mm, or they did not include documentation of the parent vessel or device size. 4,[6][7][8] Our current series of 12 patients demonstrated that the use of these small devices is technically feasible and safe, with excellent clinical and radiologic outcomes at a median latest follow-up of 1.5 years. The rates of occlusion (75%) and near-or complete occlusion (92%) are similar to overall data published for flow-diversion treatment (76% complete occlusion at 1 year), 9 and our current series comprises 50% posterior circulation aneu- rysms, which are known to carry higher rates of complications.…”
Section: Discussionmentioning
confidence: 79%
“…Pistocchi et al 1 reported a series of 26 patients, most of whom were treated with flow-diversion devices of Յ3 mm, with good outcomes including an occlusion rate of 83% and a neurologic complication rate of 4% with no hemorrhage. Yavuz et al 4 recently reported 25 cases of MCA aneurysms located at the bifurcation or more distally, with an occlusion rate of 84% and only 1 case of long-term neurologic impairment, which was mild (mRS 1). Presumably, many of the cases in this series involved small-diameter parent vessels and PEDs, but these specific data were not reported.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation